DESAIN PASAR PAKAIAN BEKAS DAN TERMINAL BUS SENEN DENGAN KONSEP FASHION ARCHITECTURE, DRIVE-THRU, DAN PARK & RIDE - Widyanti, Metta; Lianto, Fermanto (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
Pasar Senen, one of Jakarta’s oldest markets, has an area called Pasar Malam Senen, which is open from night until dawn. In this area, sellers sell second-hand clothes on the side of a main road, creating an unsafe and uncomfortable situation because the area is congested with vehicles. A similar problem occurs at the Senen Bus Terminal, which has not yet undergone revitalization, maintaining disorganized conditions and making it uncomfortable for users. The problem was identified as how to improve the image of the Pasar Malam Senen and Senen Bus Terminal with Fashion Architecture to meet user needs. This research aims to improve the image of both by applying Fashion Architecture and Drive-Thru. This research uses descriptive analysis methods to analyze data from interviews and direct observation at Senen Night Market and Senen Bus Terminal. Programs from both locations were combined into one large program to design a building that integrated the two. The result is a building design that combines the concepts of Fashion Architecture, a Drive-Thru second-hand clothes market, and a bus terminal in Senen. Drive-Thru is implemented to meet the daily needs of Senen Night Market sellers and buyers, with goods displayed on the road without the need to get out of the vehicle. The building design includes a corrugated roof and second skin. With this approach, it is hoped that the image of the Bus Terminal and second-hand Clothing Market in Senen can improve while meeting user needs. Keywords: drive-thru; fashion architecture; park and ride; second-hand clothes market; terminal Abstrak Pasar Senen, salah satu pasar tertua di Jakarta, memiliki area bernama Pasar Malam Senen, yang buka dari malam hingga subuh. Di area ini, pedagang berjualan pakaian bekas di jalan raya menciptakan situasi jual-beli tidak aman dan nyaman dikarenakan area padat dengan kendaraan. Masalah serupa terjadi di Terminal Bus Senen yang belum mengalami revitalisasi, mempertahankan kondisi tidak tertata dan kumuh sehingga tidak nyaman bagi penggunanya. Diidentifikasi masalah bagaimana meningkatkan citra Pasar Malam dan Terminal Bus Senen dengan Fashion Architecture agar memenuhi kebutuhan pengguna. Penelitian ini bertujuan meningkatkan citra keduanya dengan mengaplikasikan Fashion Architecture dan Drive-Thru. Penelitian ini menggunakan metode deskriptif analisis untuk menganalisis data dari wawancara dan observasi langsung di Pasar Malam Senen dan Terminal Bus Senen. Program-program dari kedua lokasi digabungkan menjadi satu program besar untuk merancang bangunan yang mengintegrasikan keduanya. Hasilnya adalah desain bangunan yang memadukan konsep Fashion Architecture, Drive-Thru pasar pakaian bekas, dan terminal bus di Senen. Drive-Thru diterapkan untuk memenuhi kebutuhan harian penjual dan pembeli Pasar Malam Senen, dengan barang dipajang di jalan raya tanpa perlu turun dari kendaraan. Desain bangunan mencakup atap bergelombang dan second skin. Dengan pendekatan ini, diharapkan citra Terminal Bus dan Pasar Pakaian Bekas di Senen dapat meningkat sambil memenuhi kebutuhan pengguna.